Fuzzy homogeneity measures for path-based colour image segmentation. (2nd June 2006) - Chamorro-Martinez, J.; Sanchez, D.; Prados-Suarez, B.; Galan-Perales, E.
In this paper we propose a set of measures to model the concept of homogeneity in path-based image segmentation. We introduce the idea of path homogeneity as the aggregation of resemblances between consecutive pixels in the path. This resemblance is obtained from a measure of resemblance between neighbour pixels. In order to aggregate these resemblance values we propose the use of certain families of t-norms that verify a set of intuitive properties. We have studied the performance and behaviour of these functions through a set of experiments. Finally, we have applied these proposals to obtain fuzzy segmentations from real images.